LAPORAN AKUNTANSI ISLAM BUKAN SEKEDAR PERTANGGUNG JAWABAN SOSIAL - Windari Windari (Institut Agama Islam Negeri Padangsidimpuan, 2016)
Goals to be achieved in this article to see Islam Accounting Report is not just a social responsability. The study of literature is a major source, regarding various provisions of studies that have been done before, and is supported by studies published by various institutions in the form of journals and other scientific studies. Reporting in sharia accounting is not only concerned about human beings, but also all the creatures in the universe, including the creator and we believe that Islam as a way of life, especially in business activities.